Couple wed for 50 years (Raton Range Raton, New Mexico, 1986)
Newspaper Article on the 50th Anniversary of Charlie and Ruth Bada.
Master list item #: 21
File location is in the Raton File Cabinet
Keywords: Bada, Charlie; Bada, Ruth; Bada, Charles; Bada, Delena; Local History; Biography; Life and Customs; Marriage; Celebration; Anniversary; Raton, New Mexico; Farley, New Mexico; Springer, New Mexico